KREATIF ECOTOURISM KUNCI KEBERLANJUTAN PARIWISATA PULAU: STUDI KASUS KEPULAUAN GILI MATRA - I Made Murdana (Jurnal Ilmiah Hospitality, 2019)
The tourism development paradigm has a very frightening effect on the island's destination. Gili Matra Islands as an island destination has the potential to have a high level of vulnerability. The sustainability aspect of island destination is a development challenge in future. Destination protection is important in its sustainability. Creative ecotourism as a form of sustainable tourism is consistently urgent to adopted and as the purpose of this paper. The method of this paper is descriptive qualitative through in-depth interviews. Within case study of the Gili Matra Islands on this paper, it is able to provide an overview of alternative ecotourism forms in actual and conceptual of destination protection. The creative of ecotourism concept is able to collaborate with the differentiation of tourism products in each island (Gili Trawangan, Gii Meno, and Gili Air).